Robotic additive manufacturing (RAM) with clay using topology optimization principles for toolpath planning: the example of a building element. (3rd March 2020) - Kontovourkis, Odysseas; Tryfonos, George; Georgiou, Christos
ABSTRACT: The term Robotic Additive Manufacturing (RAM) describes the process of material deposition in layers, leading to solidified products using industrial robots. Similar processes like construction-scale 3D printing have gained considerable attention during the last few decades and today an increasing interest is observed. Despite their emerging trend, very early adoptions are visible today, with issues under further consideration to include construction time and cost, associated with material minimization and structural efficiency, but also ecological aspect of materials evolved. This paper discusses the current role of 3D printing in the architecture and construction and proposes a framework for implementation using Topology Optimization (TO) principles and clay-based materials. This is applied in a case study example where the design and fabrication of a building element is conducted. The results derived from this investigation are critically discussed and conclusions are drawn for a new and more effective application in the architecture and construction industry.